2003
DOI: 10.1038/sj.bjc.6600883
|View full text |Cite
|
Sign up to set email alerts
|

Irinotecan plus raltitrexed vs raltitrexed alone in patients with gemcitabine-pretreated advanced pancreatic adenocarcinoma

Abstract: There is no established second-line treatment for advanced pancreatic cancer after gemcitabine failure. In view of the urgent need for such therapy, and since preclinical and phase I clinical data suggest an encouraging, potentially synergistic activity between raltitrexed and irinotecan, the present randomised phase II study was initiated. A total of 38 patients with metastatic pancreatic adenocarcinoma, who progressed while receiving or within 6 months after discontinuation of palliative first-line chemother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
51
0
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(61 citation statements)
references
References 20 publications
5
51
0
5
Order By: Relevance
“…The present study reports the findings on a single center cohort of patients who received second-line gemcitabine treatment for advanced-stage pancreatic adenocarcinoma. A survival of 3.6 months with second-line chemotherapy was observed, which is in agreement with previous published data (Table I) (7)(8)(9)(10)14,15,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Response to gemcitabine therapy at the first follow-up evaluation (at 2 months) impacted significantly the OS of the patients.…”
Section: Discussionsupporting
confidence: 81%
“…The present study reports the findings on a single center cohort of patients who received second-line gemcitabine treatment for advanced-stage pancreatic adenocarcinoma. A survival of 3.6 months with second-line chemotherapy was observed, which is in agreement with previous published data (Table I) (7)(8)(9)(10)14,15,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Response to gemcitabine therapy at the first follow-up evaluation (at 2 months) impacted significantly the OS of the patients.…”
Section: Discussionsupporting
confidence: 81%
“…The results of previous studies concerning oxaliplatin (15), ralitrexed (16), paclitaxel (17) and pemetrexed (18) monotherapies in the second-line treatment of pancreatic cancer have revealed modest antitumor effects with no survival benefit. Studies have also reported combination chemotherapeutic regimens as second-line therapies for advanced pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Several phase II studies have evaluated different combinations of cytotoxic agents in order to improve the proportion of objective responses and the duration of survival. Numerous phase II studies have investigated combinations of these active drugs with or without gemcitabine in patients with advanced/metastatic pancreatic cancer (Rothenberg et al, 1998;Bahadori et al, 1999;Hidalgo et al, 1999;Rocha-Lima et al, 1999;Heinemann et al, 2000;Stathopoulos et al, 2001;Alberts et al, 2002;Berlin et al, 2002;Hess et al, 2003;Stathopoulos et al, 2003;Ulrich-Pur et al, 2003). The combination of gemcitabine plus irinotecan has resulted in an objective response of 25% with a median overall survival ranging from 5.7 to 7 months (Rocha-Lima et al, 2002;Stathopoulos et al, 2004).…”
mentioning
confidence: 99%
“…Despite the fact that the achieved objective response rate with gemcitabine-based combinations is practically similar, there are controversial results concerning overall survival; the 1-year survival was reported to be 22% with the gemcitabine -irinotecan combination (objective response rate (ORR) 25%) whereas overall survival was found to be 34.8% with the gemcitabine -capecitabine combination (ORR 18.9%) (Stathopoulos et al, 2003;Ulrich-Pur et al, 2003).…”
mentioning
confidence: 99%